Nutrient transfers from livestock in West African agricultural systems - Leeuw, P.N. de; Reynolds, L.; Rey, B. (International Livestock Centre for Africa, 1995)
The potential supply of nutrients from excreta voided by livestock and what is potentially available for transfer to cropland are examined within a West African context. Nutrient output from cattle is derived from a simulation model that predicts nutrient intake in relation to animal performance and monthly feed supplies; it subsequently links intake to excreted output of lactating and dry cows and young growing stock, as well as of entire cattle herds. The supply side of potential nutrient transfers is addressed at several scales, from agro-ecological zones to that of individual farmers, by analysing rations between livestock and farmed and non-farmed land. At a regional scale, focus is on Nigeria and on the cottonbelt in francophone West Africa. The Nigerian situation elucidates the relationships between livestock and land along the rainfall gradient and brings out the multiple interactions between settled smallholder farmers and more mobile agropastoral and transhumant herders. Farming systems in the cottonbelt demonstrate the importance of animal traction and cash cropping as determinants of nutrient-transfer patterns. At the farm level, three case areas are analysed: two in the cottonbelt of Mali and Cote d'Ivoire and one in the closely settled zone in semi-arid Nigeria. These analyses highlight the variable scenarios of nutrient transfers at the farm and village level, demonstrating that heterogeneity among farmers is as much at play as differences between zones and countries. The implications of these nutrient-transfer scenarios are discussed with emphasis on crop-livestock interactions at increasing levels of population pressure and how they may affect pathways of land-use intensification and soil-fertility maintenance.